The Da'wah Journey of the Prophet Muhammad SAW (Imitating the Perseverance and Never Giving Up of the Prophet Muhammad and His Companions) - Syahru Ramadhan; Hayatun Sabariah (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Muhammad bin Abdullah is one of the noblest prophets of Allah. He is a figure who is loved by Muslims throughout the world. His life story is not easy, an orphan who was given the mandate to improve the morals of every human being on earth. We can emulate his persistence in spreading Islamic teachings with his noble friends as Muslims who miss and love him. It is not easy to spread the religion of Islam, there were many obstacles and obstacles that the Prophet and his companions faced; threats of death, sabotage, excommunication, deception, slander and so on. But thanks to their persistence, today Islam is one of the largest religions in the world.